ZOYA PRODUCT PURCHASE DECISION : THE ROLE OF HALAL LOGO, PRODUCT QUALITY, AND BRAND EXPERIENCE (CASE STUDY OF STUDENT IN SURABAYA) - Candraningrat; Denis Fidita Karya; Endah Budi Permana Putri (Journal of Halal Research, Policy, and Industry, 2022)
The role of Shari'a in Muslims is to regulate Muslims following their nature. One of the things regulated in the Shari'a is how to dress. Currently, Indonesia is entering the era of globalization in the media industry, where the development of lifestyle and fashion is developing very fast. How to dress, or what is often called fashion, is an inseparable part of one's appearance. Fashion is not only in the form of clothes worn, but now fashion has a meaning as self-identity. The emergence of various types of fashion that have developed in society has caused Muslims to experience guidance in following the development of existing fashion. Moreover, Islamic law requires Muslims to choose a dress that is by the law. Therefore this study examines the effect of the halal logo, product quality, and brand experience on purchasing decisions for Zoya products. This study uses a quantitative method using a purposive random sampling method. Data collection used a questionnaire distributed to 150 Surabaya students who had never bought Zoya products. The data obtained were then analyzed using Partial Least Square (PLS). The results of this research, namely the halal logo, product quality, and brand experience, significantly influence purchasing decisions for Zoya products.